Trading volume, returns, and the disposition effect: Evidence from the London Stock Exchange - Rantasaari, Janne (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Studies originating from the perspective of classical finance theory have traditionally presented stock markets efficient and market actors rational. In the recent decades, however, behavioral finance has challenged this classical view and tried to model investors in a more accurate way combining finance, sociology and psychology. Much of research in behavioral finance concerns different kinds of biases that investors appear to have. One of such biases is the disposition effect, which refers to investors’ tendency to realize gains rather quickly but avoid realizing losses. This study takes a look at volume, returns, and the disposition effect from the viewpoint of behavioral finance. The study is interested both in the informational value that volume may have and the impact that the disposition effect may have on volume and returns. The study uses two data sets from the London Stock Exchange in order to examine the disposition effect’s impact on post-IPO (initial public offering) trading volumes and on stock returns in general. The research is conducted using regression analyses in order to study the variance in volume and returns possibly caused by the disposition effect. The first part of the empirics concerning mainly IPO trading volume is largely based on an earlier study conducted by Kaustia (2004). The latter part concerning mainly stock returns is largely based on a study conducted by Grinblatt and Han (2005). The first data set analyzed consists of 44 companies that had their IPO between 1.1.2005 and 31.12.2013. The second data set consists of 72 companies that were constituents of the FTSE 100 index in the autumn of 2015. The data used in the study is gathered from SDC Platinum and Datastream. The study contributes to the growing literature in the field of behavioral finance by providing further evidence for the presence of the disposition effect in the stock markets. Based on the regression analyses conducted, the disposition effect seems to have an impact on post-IPO trading volume as well as on stock returns. The results indicate that trading volume is not irrelevant but has informational value. Furthermore, it is theorized that volume might have a role in mediating the impact of the disposition effect on returns. Some uncertainty is, however, included in the results due to the restrictions set by the statistical methods chosen. This limits the extent to which definitive conclusions about the results can be drawn.